2006
DOI: 10.1002/mds.20968
|View full text |Cite
|
Sign up to set email alerts
|

Association between amantadine and the onset of dementia in Parkinson's disease

Abstract: The objective of this study is to compare the occurrence of dementia among Parkinson's disease (PD) patients treated with amantadine (AM group) with those never exposed to it (NoAM group). PD dementia shares neuroanatomical and biochemical similarities with Alzheimer's disease (AD). Memantine, an N-methyl-D-aspartate (NMDA) receptor antagonist has been shown to be beneficial in AD. Memantine is a dimethyl derivative of amantadine, which also possesses NMDA receptor blocking properties. We hypothesized that ama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 37 publications
1
34
0
2
Order By: Relevance
“…y-Axis, % of samples in that year containing these mutations; x-axis, year of sample collection. seasonal influenza viruses to patients with chronic neurological disorders (e.g., Parkinson's disease), who are on long-term, repeat prescriptions for amantadane [Luginger et al, 2000;Del Dotto et al, 2001;Thomas et al, 2004;Inzelberg et al, 2006;Reis et al, 2006]. Secondly, widespread, yet sporadic use of amantadane for the treatment of influenza may have contributed to the selection of adamantane-resistant viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…y-Axis, % of samples in that year containing these mutations; x-axis, year of sample collection. seasonal influenza viruses to patients with chronic neurological disorders (e.g., Parkinson's disease), who are on long-term, repeat prescriptions for amantadane [Luginger et al, 2000;Del Dotto et al, 2001;Thomas et al, 2004;Inzelberg et al, 2006;Reis et al, 2006]. Secondly, widespread, yet sporadic use of amantadane for the treatment of influenza may have contributed to the selection of adamantane-resistant viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Amantadane has been used to treat dyskinesia in patients with Parkinson's disease [Luginger et al, 2000;Del Dotto et al, 2001;Thomas et al, 2004;Reis et al, 2006], as well as showing some benefits in delaying the onset of Parkinson's dementia [Inzelberg et al, 2006]. However, it was first investigated as an antiviral drug against influenza [Reis et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…471 Another study found that amantadine may delay the onset of dementia in patients with PD, and attenuate its severity. 472 Chase and Oh 473 have proposed that amantadine might also have antidyskinetic effects because of its NMDA receptor antagonist property. They hypothesized that levodopa-induced pulsatile stimulation of dopamine receptors on MSNs induces abnormal phosphorylation of NMDA receptors leading to glutamate-mediated plastic changes and the development of motor complications.…”
Section: Modest Antiparkinsonian Effectmentioning
confidence: 99%
“…Amantadine has been used for the treatment of Parkinsonism for more than 30 years and has been reported to influence longevity 23 and cognitive decline 24 in PD. In spite of its common use for gait disturbances, there are very few objective assessments of its effectiveness.…”
Section: Amantadinementioning
confidence: 99%